Social Media Marketing : Strategies for Engaging in Facebook, Twitter & Other Social Media - Evans, Liana "Li" (India Pearson Education, 2011)
Using new social media marketing techniques, you can deepen relationships with your most passionate, profitable customers and create more of them than ever before! In this 100% practical book, world-renowned expert Li Evans shows exactly how to make the most of social media in any company, in any industry. You'll discover exactly how to customize your best social networking strategy then staff it, organize it, manage its risks, and execute it successfully. Evans shows how to understand your audience, enter the conversation, build trust, protect your brand, integrate social media into existing marketing programs, measure your results and profit big from today's hottest new social media sites and platforms
Include Index
Keywords: Social marketing -- Internet marketing